PENGARUH AUDIT DELAY TERHADAP KUALITAS AUDIT DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TRANSPORTASI YANG LISTING DI BURSA EFEK INDONESIA - Sari, Devika Miranda (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study analyzes the influence of Audit Delay on audit quality with company size as moderating. This research was conducted at a Transportation company listed on the Indonesia Stock Exchange (IDX) in 2014-2017. The data source used in this study is secondary data. The research population is 28 companies by analyzing financial statements from 2014-2017 which are accessed by the BEI official website, www.idx.co.id. The sampling technique used was Purposive sampling technique with a sample of 112 companies. The data analysis tool uses Multiple Linear Regression. The research findings reveal that the audit delay variable is not affected by the audit quality variable, therefore the less likely the Audit Delay is, the better the audit quality. Research also shows that the size of the company has a partial effect on audit quality, the greater the size of the company, the better the level of audit quality. This study found that firm size does not moderate the relationship between audit delay variables and audit quality variables, but the size of the company influences audit quality, the size of the company in this study acts as an independent variable.